Critical review on electrooxidation and chemical reduction of azo dyes: Economic approach - Kamenická, Barbora; Vagenknecht, Gabriela (My University, 2024)
Effective degradation technologies have been extensively investigated and used to remove azo dyes from wastewater for decades. However, no review dealing with both electrooxidation and chemical reduction of azo dyes from an economic and, therefore, application-relevant perspective has been found in the current literature. A novelty of this review article consists not only in the brief summarization and comparison of both methods but mainly in the evaluation of their economic side. Based on the literature survey of the last 15 years, the costs of treatment approaches published in individual research articles have been summarized, and the missing data have been calculated. A broad spectrum of advanced electrode materials and catalysts have been developed and tested for the treatment, specifically aiming to enhance the degradation performance. An outline of the global prices of electrode materials, reducing agents, and basic chemicals is involved. All additional costs are described in depth in this review. The advantages and disadvantages of respective methods are discussed. It was revealed that effective and cheap treatment approaches can be found even in advanced degradation methods. Based on the collected data, electrooxidation methods offer, on average, 30 times cheaper treatment of aqueous solutions. Concerning chemical reduction, only ZVI provided high removal of azo dyes at prices <100 $ per kg of azo dye. The factors affecting total prices should also be considered. Therefore, the basic diagram of the decision-making process is proposed. In the conclusion, challenges, future perspectives, and critical findings are described.
Kritický přehled elektrooxidace a chemické redukce azobarviv: Ekonomický přístup
Keywords: Azo dye; Electrochemical oxidation; Chemical reduction; Cost estimation; Economy; azo barvivo; Elektrochemická oxidace; Chemická redukce; Odhad nákladů; Ekonomika